Proceedings of the 15th International Symposium on Management (INSYMA 2018) 2018
DOI: 10.2991/insyma-18.2018.31
|View full text |Cite
|
Sign up to set email alerts
|

Internal communication, employee participation, job satisfaction, and employee performance

Abstract: The main objective of this research was to examine relationship between internal communication, employee participation, job satisfaction, and employee performance. The samples of this study were 489 state officials from 10 city municipalities in Chonburi (Thailand). Questionnaire was employed to collect the primary data which later were analyzed using structural equation modeling technique. The results indicated that internal communication had positive influence on employee participation and job satisfaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…This result also in line with other studies which stated that job satisfaction does not influence the job performance of service workers on McConnell Dowell Services Company (Parlaungan and Ramadhan, 2019). Similar research results were also found by Kulachai et al, (2018), Putri (2018), and Husein and Hanifah (2019) who stated that job satisfaction did not significantly influence job performance.…”
Section: Jobsupporting
confidence: 91%
“…This result also in line with other studies which stated that job satisfaction does not influence the job performance of service workers on McConnell Dowell Services Company (Parlaungan and Ramadhan, 2019). Similar research results were also found by Kulachai et al, (2018), Putri (2018), and Husein and Hanifah (2019) who stated that job satisfaction did not significantly influence job performance.…”
Section: Jobsupporting
confidence: 91%
“…Furthermore, Vercic et al explained that effective internal communication contributes positively to employee work performance which in turn can improve organizational performance. This is supported by the statements of experts who find a positive correlation between internal communication and employee performance (Bhatia and Balani, 2015;Kulachai et al, 2018). In addition, organizational leaders need to utilize various kinds of internal communication media to convey messages, ranging from face-to-face communication, print media, electronic media, and social networking media.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Carrière and Bourque's (2009) data showed that internal communication practices explain 49.8% of the variation in communication satisfaction, 23.4% of the variation in job satisfaction, and 17.5% of the variation in affective organizational commitment and that these effects are fully mediated by communication satisfaction when job satisfaction and affective organizational commitment were regressed against both internal communication practices and communication satisfaction. The results of Kulachai et al (2018) indicated that internal communication has a positive influence on employee participation and job satisfaction, with employee participation and job satisfaction playing a mediating role between internal communication and job performance. They further concluded it can be implied that internal communication would enhance employees' job satisfaction.…”
Section: Discussionmentioning
confidence: 97%